PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD KELAS RENDAH - Isniatun Munawaroh (Jurnal Penelitian Ilmu Pendidikan, 2010)
Giving the less of critical thinking skills in the learning process could direct students to the habit of doing any activities without knowing the purpose and objective and the tendency why they are doing those activities. This will lead to the need of some efforts to develop the critical thinking skills through learning, which can be facilitated by thematical learning. The aspects of thematical learning facilitate the creating of chance for students to see and build the relationship of information conceptual between subject matters that would benefit to help developing students' critical thinking skills. The model of thematical learning to develop students' critical thinking skills is resulted from the research that consists of planning, implementation, and evaluation. The planning of thematical learning to develop critical thinking skills comprises of mapping the basic competencies, developing theme network, developing the syllabus, and organizing the RPP (Learning Implementation Planning). The implementation of thematical learning resulted from the development consists of introductory stage that comprises of two steps that are learning warm-up and theme orientation. The core stage consists of five steps, which are exploring and delivering the material, proposing the problem, searching the information, discussing and performing the work. The final stage comprises of one step, which is conclusion. The evaluation of thematical learning to develop critical thinking skills is evaluating the process and learning result. Key words: Thematical Learning Model, Critical Thinking